INFORMATION SYSTEMS PRACTICE FOR DEVELOPMENT IN AFRICA - Korpela, Mikko; de la Harpe, Retha; Soriyan, H. Abimbola; Macome, Esselina; Mursu, Anja (IFIP International Federation for Information Processing, 2023)
IFIP International Federation for Information Processing, p.16-35.